Utilizing Used Cooking Oil for Aromatherapy Candle Production: Pemanfaatan Minyak Goreng Bekas untuk Produksi Lilin Aromaterapi (Indonesian Journal of Cultural and Community Development, 2024)
Background: Environmental pollution from used cooking oil poses significant challenges. Specific Background: Improper disposal of this waste contributes to ecological damage, highlighting the need for effective recycling solutions. Knowledge Gap: Community awareness and skills in transforming used cooking oil into valuable products are limited. Aims: This study aimed to train local residents in recycling used cooking oil into aromatherapy candles, reducing pollution and enhancing economic prospects. Results: The training, facilitated by university students, successfully informed participants about the hazards of used cooking oil and demonstrated candle-making. Participants reported high satisfaction and a willingness to apply their new skills. Novelty: This initiative presented a practical method for converting waste into a marketable product, addressing both environmental and economic issues. Implications: The program not only raised environmental awareness but also empowered the community with sustainable business opportunities, fostering innovation in waste management and improving local economies.Highlights : • Pelatihan mengajarkan keterampilan mengolah limbah minyak menjadi produk bernilai.• Inisiatif ini meningkatkan kesadaran lingkungan di masyarakat.• Produk lilin aromaterapi berpotensi meningkatkan perekonomian lokal.Keywords: Pencemaran, Minyak, Lilin, Aromaterapi, Pelatihan